Performance analysis of ewe and lambs Ile de France - Costa, Ana Lúcia Barreto da (2022)
Sheep production systems in Rio Grande do Sul are diversified. Thus, some reproductive and productive indices of the herd become smaller than the potential of the herds. The aim of this study was to evaluate the productive performance of Ile de France ewes and lambs reared extensively in a native field located in the Northeast mesoregion of Rio Grande do Sul. The experiment was developed in Cabanha Lagoa, located in the municipality of Capão Bonito do Sul. Data from of 33 Ile de France sheep and 37 lambs. The data refer to the production cycles of lambs born in 2018 and performance of sows from the 2019 production cycle followed up to 340 days of life. When evaluating the efficiency of the dams, taking into account the sex of the lambs, it was found that there was no significant difference for both birth and weaning weight. For the efficiency of the dams according to the type of birth (single-born or multiple-born), it was possible to identify that the efficiency of the ewe at birth (Efp) was higher in multiple-born. Lambs from single-born, on the other hand, had greater weight in kg than lambs from multiple-born. Dams from multiple-born presented superior performance (104% of their weaned weight) in relation to productive efficiency when compared to dams from single-born (65% of their weaned weight). With regard to weight evolution, lambs from single-born obtained higher weights in a shorter time, compared to lambs from multiple-born.